Sustainable Biomass-Derived Cellulose/HKUST-1 Composite from Purun (Lepironia articulata): Synthesis and FTIR Characterization - Siti Unvaresi Misonia Beladona; Irvan Maulana Fiqih; Laila Zahra; Diah Panjar Arum; Achmad Ripai (Yayasan Literasi Sains Indonesia, 2026)
This study explores the fabrication of a cellulose/HKUST-1 composite derived from purun (Lepironia articulata), a wetland biomass abundant in cellulose and promising as an eco-friendly feedstock for advanced materials. HKUST‑1, a copper-based metal-organic framework known for its high porosity, suffers from reduced stability in humid environments. To address this limitation, a composite integrating purun-derived cellulose with HKUST‑1 was synthesized and subsequently characterized using Fourier Transform Infrared (FTIR) spectroscopy. Cellulose was isolated via alkaline delignification and peroxide bleaching with a yield of 26.68%. HKUST-1 was synthesized using a solvothermal method, producing a turquoise-blue material with a yield of 70.96%. The composite was prepared using an ex-situ method, resulting in a green-colored product with a yield of 85.90%. FTIR analysis confirmed HKUST-1 formation through the disappearance of the C=O band ( 1719 cm⁻¹) and the appearance of COO⁻ bands ( 1560-1600 and 1450 cm⁻¹), along with Cu-O vibration ( 725 cm⁻¹). FTIR analysis of the composite revealed the presence of diagnostic peaks attributable to both cellulose and HKUST‑1, confirming successful incorporation without compromising structural integrity. Notably, the O‑H stretching band appeared broadened and slightly shifted, indicating hydrogen-bond interactions between cellulose and HKUST-1. These results demonstrate that purun-derived cellulose is a sustainable matrix for HKUST-1 with potential in adsorption applications.